(untitled) (Annals of Medical Research, 2023)
Aim: The aim of the study is to examine tuberculosis and endocrine-related deaths worldwide from WHO ICD-10 data with multi-country comparisons. Materials and Methods: ICD-10 mortality data of WHO was used. Given mortality codes were examined, and mortality data records for 14 countries between 1996 and 2017 were used. Results: For people over 60 ages, the most common mortality was reported for endocrine, nutritional and metabolic diseases, followed by respiratory related deaths. Respiratory related mortality is the most dominant mortality among other tuberculosis mortality and endocrine, nutrition and metabolic diseases related mortality. The most frequent mortality was reported in 2005, followed by 2004 and 2003. Infant deaths and 60 and above age mortality differences between gender groups were statistically insignificant for all mortality causes of the research (p>0.05). For under 60 ages, respiratory and other tuberculosis related mortalities were significantly higher in the male patients (p<0.05). Cause, year and country parameters were determinants of infant mortality with statistically significant rates (p<0.05). However, effect of gender on infant mortality for research causes was insignificant (p>0.05). For under 60 age group; cause, gender, year and country parameters had significant effect on mortality rates (p<0.05). Cause, gender, year and country parameters were not effective on mortalities above 60 ages (p>0.05). Conclusion: Although there is no sufficient data to establish a direct relationship on TB-related deaths and endocrine-related deaths, the occurrence of both diseases in similar countries according to the World Bank development evaluation with same trends indicates the questioning of the relationship between these two disease groups.